Contemplating human-centred security & privacy research: Suggesting future directions. (June 2017) - Renaud, Karen; Flowerday, Stephen
Abstract: This position paper is a reflective look at the state of Human-Centred Security & Privacy (HCSP) research and the paradigms that have informed and driven the research. It is important to reflect and examine, because, as Harrison et al. [1] argue, with respect to HCI, " the lack of clarity about the epistemological distinctions between paradigms is a limiting factor in the development of the field " (p. 1). We discuss the current state of play and then suggest possible explanations and suggestions for the way forward for our research field. This paper aims to prompt a discussion of the directions HCSP should take, and ways we could deploy to encourage maturation of the field.